Battle Angel Alita. Vol. 5 - Kishiro, Yukito (Kodansha Comics, 2018)
In a dump in the lawless settlement of Scrapyard, far beneath the mysterious space city of Zalem, disgraced cyber-doctor Daisuke Ido makes a strange find: the detached head of a cyborg woman who has lost all her memories. He names her Alita and equips her with a powerful new body, the Berserker. While Alita remembers no details of her former life, a moment of desperation reawakens in her nerves the legendary school of martial arts known as Panzer Kunst. In a place where there is no justice but what people make for themselves, Alita decides to become a hunter-killer, tracking down those who prey on the weak. But can she hold onto her humanity as she revels in her bloodlust? This FINAL VOLUME includes the rare, acclaimed story ASHEN VICTOR, plus two extensive interviews with creator Yukito Kishiro and all of the canon and non-canon endings of the original cyberpunk classic, Battle Angel Alita !